SDGs-Based STEM Learning Integration in Elementary School: a Systematic Literature Review - Ani Rosidah; Eko Handoyo; Barokah Isdaryanti (Universitas Negeri Semarang, 2026)
The integration of Sustainable Development Goals (SDGs) in Science, Technology, Engineering, and Mathematics (STEM) learning in Elementary Schools (SD/MI) is an important step to instill sustainability awareness, understanding of climate change, and critical thinking skills from an early age. This study aims to identify integration patterns, learning approaches, obstacles, and learning outcomes in the implementation of STEM-based SDGs in elementary education. The method used is a Systematic Literature Review (SLR) with reference to the PRISMA 2020 protocol. Literature was obtained from Scopus, Web of Science, ERIC, and Google Scholar databases in the period 2015–2025. The results of the study indicate that the integration of SDGs in STEM learning can direct science education not only to mastery of skills, but also the formation of global citizens who care about sustainability. Optimal implementation requires collaborative teacher training, a contextual curriculum, and a holistic formative assessment system.